The Effect of Hypnobirthing Relaxation on the Anxiety Level of Primigravida Mothers in the Third Trimester in Facing Childbirth Preparation at Bpm Nurlina Sirait, Sst Dumai City in 2023 - Juwanti, Dwi (Cattleya Darmaya Fortuna, 2024)
The purpose of this study was to determine the effect of hypnobirthing relaxation on the anxiety level of primigravida mothers in the third trimester in facing labor preparation. The method used was quasi-experimental research involving 20 primigravida mothers selected through random sampling technique. The intervention was carried out by providing hypnobirthing sessions, and anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before and after the intervention. The main results showed that there was a significant effect of hypnobirthing relaxation on reducing anxiety levels, with a p value = 0.001, which indicates that this intervention is effective in reducing anxiety in pregnant women. The practical implication of this study is that hypnobirthing can be used as a useful method to help primigravida mothers overcome anxiety before childbirth, so it is recommended for health workers to integrate this technique in childbirth preparation programs.